2019
DOI: 10.3390/nu11030557
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vegetarian and Vegan Diet during Pregnancy on the Health of Mothers and Offspring

Abstract: Vegetarian and vegan diets have increased worldwide in the last decades, according to the knowledge that they might prevent coronary heart disease, cancer, and type 2 diabetes. Althought plant-based diets are at risk of nutritional deficiencies such as proteins, iron, vitamin D, calcium, iodine, omega-3, and vitamin B12, the available evidence shows that well planned vegetarian and vegan diets may be considered safe during pregnancy and lactation, but they require a strong awareness for a balanced intake of ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
148
1
32

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(202 citation statements)
references
References 149 publications
4
148
1
32
Order By: Relevance
“…For the most part, ID in premenopausal women results primarily from an imbalance between nutritional iron intake and physiologic blood loss through menses or previous pregnancy. Decreased dietary iron intake can contribute to this imbalance, as in women following a vegetarian or vegan diet who do not use an iron supplement, or who have iron malabsorption [37,38]. Menstrual blood loss can represent 25-50 mg iron per cycle [33] depending upon the patient's Hct/Hb concentration and the individual pattern of menstruation, and can be substantially greater in patients with menorrhagia [39].…”
Section: Id In Premenopausal Womenmentioning
confidence: 99%
“…For the most part, ID in premenopausal women results primarily from an imbalance between nutritional iron intake and physiologic blood loss through menses or previous pregnancy. Decreased dietary iron intake can contribute to this imbalance, as in women following a vegetarian or vegan diet who do not use an iron supplement, or who have iron malabsorption [37,38]. Menstrual blood loss can represent 25-50 mg iron per cycle [33] depending upon the patient's Hct/Hb concentration and the individual pattern of menstruation, and can be substantially greater in patients with menorrhagia [39].…”
Section: Id In Premenopausal Womenmentioning
confidence: 99%
“…There are, however, some nutritional concerns associated with reducing the levels of animal products in the human diet [59]. In particular, plant-based diets are often deficient in important macronutrients and micronutrients, including high-quality proteins, omega-3 fatty acids, vitamin B 12 , vitamin D, iron, calcium, and iodine [60,61]. Over time, deficiencies in these nutrients could lead to health problems, particularly in infants and the elderly [60,62].…”
Section: Nutritional Fortificationmentioning
confidence: 99%
“…In particular, plant-based diets are often deficient in important macronutrients and micronutrients, including high-quality proteins, omega-3 fatty acids, vitamin B 12 , vitamin D, iron, calcium, and iodine [60,61]. Over time, deficiencies in these nutrients could lead to health problems, particularly in infants and the elderly [60,62]. Consequently, it would be advantageous to supplement plant-based diets with these critical nutrients so as to avoid these deficiencies.…”
Section: Nutritional Fortificationmentioning
confidence: 99%
“…Donor milk is often used in the absence or insufficiency of the mother's milk. The composition of human milk varies throughout the lactation period as a result of internal and external factors, such as gestational age, maternal body mass index (BMI), smoking status, and even diet [1][2][3][4][5]. Past studies have demonstrated that the duration of lactation is a primary determinant of some nutrient contents, such as proteins and sodium [1,2,[6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%